Musculoskeletal work preceding the Tkachev on uneven bars - Irwin, G.; Kerwin, D. G. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to identify the mechanics of traditional outward facing (O) and newer inward facing (I) Tkachev on uneven bars. Images of ten straddle Tkachevs (O=5, I=5) performed at the Sydney Olympic Games, 2000 were recorded with twin video cameras (50Hz). Manual digitising and 3D DLT reconstruction techniques were combined with inertia modelling to develop customised profiles for the ten gymnasts. Inverse dynamics analyses were used to quantify hip and shoulder joint kinetics, and segmental and bar energy exchanges from the horizontal position on the downswing tobar release. There was evidence that more energy was stored in and recovered from the bar in the inward technique. The role of the hips remained similar for both skills, but a large shoulder flexion rather than extension occurred in the inward technique close to release.